Experimental Performance Investigation of Photovoltaic Module and Water Cooled Photovoltaic/Thermal System under Middle of Iraqi Climatic Conditions - Shahad, Haroun; Hasan Abbood, Mohammed; Jebur Dakhil, Zuhair (International Journal of Engineering and Technology, 2018)
Photovoltaic(PV) cells are one of the most important resources of renewable energy. In this paper, anexperimental comparative performance study between PV module and water-cooled photovoltaic/thermal (PV/T) solar system at  different  flowrates of (0.5, 1, 1.5, 2) L/min is presented andincluding their thermal and electrical performances. The experiments werecarried out under outdoor exposure to the climate of Hilla, Iraq(32.46 °N, 44.42 °E). Solar irradiance, the temperatures on the front surfaces and back sheet of PV and PV/T solar system, flowing water, ambient air and wind speed are measured. In addition, the electrical power of PV module and PV/T solar system is measured.The results show that the maximum enhancement ratio of electrical efficiency of the PV/T solar system compared with PV module is 18.86% in March at flowrate of 2 L/min. The minimum enhancement is 13.36 % in July at flowrate of 0.5 L/min. The maximum overall efficiency improvement ratio of PV/T solar system compared to PV module is 81% in March at flowrate of 2 L/min while the minimum improvement is 74.08% in July at a flowrate of 0.5 L/min. The maximum average of cooling water temperature rise is 11.28 °C at a flowrate of 0.5 L/min in March, while the minimum is 2.69 °C at a flowrate of 2 L/min in July.
Keywords: Solar energy; PV/T solar system; PV module; experimental investigation; comparative study; performance; cooled water.